2016
DOI: 10.1007/s12262-016-1511-0
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Cholecystitis: Analysis of 108 Patients

Abstract: The aim of this study was to evaluate the clinical and radiological features of xanthogranulomatous cholecystitis (XGC) and the results of surgical treatment. This retrospective study concerns clinical, radiological, and surgical data as well as histopathological findings and postoperative results of 108 patients with XGC who were identified after evaluating 7916 cholecystectomy specimens between 2004 and 2014 in a single institute. One hundred eight patients with XGC were evaluated (56 males and 52 females, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 24 publications
2
25
0
13
Order By: Relevance
“…Yücel et al did not emphasize the relationship between conditions causing biliary stasis and XGC in their study. However, they reported that 13.8% of the patients had ERCP, 11.1% had choledocholithiasis, 4.6% had cholangitis, and 4.6% had acute pancreatitis in the preoperative period 7 . In our study, pathologies that may lead to extrahepatic bile duct obstruction were observed in patients diagnosed with XGC 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Yücel et al did not emphasize the relationship between conditions causing biliary stasis and XGC in their study. However, they reported that 13.8% of the patients had ERCP, 11.1% had choledocholithiasis, 4.6% had cholangitis, and 4.6% had acute pancreatitis in the preoperative period 7 . In our study, pathologies that may lead to extrahepatic bile duct obstruction were observed in patients diagnosed with XGC 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation of XGC is variable and often non-specific. A majority of patients present with chronic cholecystitis while others have acute cholecystitis or Mirizzi’s syndrome [ 8 , 11 ]. Almost all patients with XGC report abdominal pain, while nausea, vomiting, and anorexia occur in 18%–38% of patients [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…XGC is thought to result from mucosal ulceration or rupture of occluded Rokitansky-Aschoff sinuses, followed by intramural extravasation of inspissated bile and mucin [ 3 , 11 ]. This can be caused by elevated intraluminal pressure secondary to gallbladder or cystic duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramural accumulation of lipid-laden macrophages and acute and chronic in lammatory cells is the hallmark of the disease. The xanthogranulomatous in lammation can be very severe and can spill over to the neighboring structures like liver, bowel and stomach resulting in dense adhesions, abscess formation, perforation, and istulous communication with adjacent bowel [1][2][3]. Cholecysto-colic istula is a rare and late complication of gallstones roughly found 1 in every 1,000 cholecystectomies.…”
Section: Introductionmentioning
confidence: 99%